The Emergence of Governance in an Open Source Community - O'Mahony, Siobhán; Ferraro, Fabrizio (Academy of Management Journal, 2007)
Little is known about how communities producing collective goods govern themselves. In a multimethod study of one open source software community, we found that members developed a shared basis of formal authority but limited it with democratic mechanisms that enabled experimentation with shifting conceptions of authority over time. When members settled on a shared conception of authority, it was more expansive than their original design. A statistical test of the predictors of leadership reinforced this finding. By blending bureaucratic and democratic mechanisms, the governance system evolved with the community's changing conceptions of authority.